Sharing individual participant data from clinical studies: a cross-sectional online survey among Italian patient and citizen groups. Issue 2 (5th February 2019) - Colombo, Cinzia; Roberto, Anna; Krleza-Jeric, Karmela; Parmelli, Elena; Banzi, Rita
Abstract : Objectives: To gather knowledge on the current debate, opinions and attitudes of Italian patient and citizen groups on individual participant data (IPD) sharing from clinical studies. Design: Cross-sectional online survey. Setting and participants: A 22-item online questionnaire was sent by email to 2003 contacts of patient and citizen groups in Italy. We received 311 responses, checked for duplicate respondents (16); 295 single groups responded, 280 providing questionnaires eligible for analysis (response rate 15%). Ninety (32.1%) dealt with oncology and palliative care, 175 (46.2%) operated locally or regionally and 136 (48.6%) were involved in clinical research. Outcome measure: Data on Italian patient and citizen groups' self-reported knowledge, attitudes and opinions on IPD sharing, mechanisms for IPD access, advantages and risks. Results: Half the respondents (144 out of 280, 51%) had some knowledge about the IPD sharing debate, and 60 (42%) stated they had an official position (35 in favour, 19 in favour with restrictions, 2 against, 1 neither for nor against, 3 missing). Nineteen discussed the topic encouraged by this survey; 39% approved broad access by researchers and other professions and identified information to participants, data de-identification, secure archives, access agreements and sanctions for misuse as important aspects of IPD sharing models. Respondents highlighted re-identification, privacy and re-use of data for purposes that participants do not agree on, as main risks, advancement of innovation and reducing waste in research as main advantages. Around half believed IPD sharing would not discourage study participation. Conclusions: Half the respondents were aware of the debate. Those who had an official position were mainly in favour of IPD sharing. Many supported broad access, asking for conditions important for building trust in entities that handle IPD sharing. Although limited by the low response rate, these findings reinforce the demand for reliable and transparent processes where accountabilities are clear.